Association between social capital and trajectories of cognitive function among Chinese older adults - Mengyun Xiong; Zhaojing Wen; Wanrui Ma; Xue Hu; Yan Tong; Zhizhong Wang (BMC Public Health)
Abstract Background The association between social capital and trajectories of cognitive function (CF) is still unclear among older adults in mainland China. The present study aims to examine the association using a longitudinal cohort from the Ningxia Healthy Aging Cohort. Methods Four waves of longitudinal data were abstracted to identify the CF trajectories using the conditional latent class growth model (LCGM). CF was measured using the Chinese version of the Mini-Mental State Examination (MMSE) from 2012 to 2023. Social capital, including social cohesion, social interaction, civic participation, and spiritual capital, was assessed using a series of standard instruments at baseline. Multinomial logistic regression was used to test the association between social capital and each trajectory class. Results Three distinct CF trajectories were identified: Stable (72.5%), slow decline (25.8%), and deterioration (1.7%). High spiritual capital was associated with a decreased risk of developing a deterioration trajectory (OR = 0.36, 95% CI = 0.14–0.93), while high civic participation (OR = 0.61, 95% CI = 0.46–0.81) was associated with a decreased risk of developing a slow decline trajectory. Low CF at baseline was the first important risk factor, followed by age, civic participation, sex, monthly income, spiritual capital, and obesity. Conclusions The CF trajectories are heterogeneous among older Chinese adults. Civic participation was associated with a lower risk of a slow decline trajectory, and spiritual capital was slightly associated with a lower risk of a deterioration trajectory. These findings support the development of social-integrated interventions for vulnerable groups.